2000
DOI: 10.1007/bf02766101
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and their metabolites in the brain and urine of rats with experimental Parkinson’s disease

Abstract: The content of catecholamines and their metabolites in the brain and the relationship between cerebral catecholamine levels and their urinary excretion were studied in rats with 6-OHDA-induced hemiparkinsonism. 6-OHDA reduced brain concentrations of dopamine, DOPAC, and homovanilic acid and urinary excretion of dopamine, dioxyphenilalanine, and DOPAC by more than 90%. A positive correlation was found between the concentrations of these metabolites in the urine and striatum. Measurement of urinary catecholamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…Also, while previous work suggested that urinary dopamine excretion is reflective of central nervous system dopamine levels (Chekhonin et al, 2000; Marc et al, 2008), it is important to acknowledge our use of urinary dopamine as a proxy measure may limit the inferences we can make about the associations between CNS dopamine, sleep, and immune status (Hinz et al, 2011). In addition, we were limited in that we had access to only one immune measure (CD4 count) and one dopamine measure.…”
Section: Discussionmentioning
confidence: 99%
“…Also, while previous work suggested that urinary dopamine excretion is reflective of central nervous system dopamine levels (Chekhonin et al, 2000; Marc et al, 2008), it is important to acknowledge our use of urinary dopamine as a proxy measure may limit the inferences we can make about the associations between CNS dopamine, sleep, and immune status (Hinz et al, 2011). In addition, we were limited in that we had access to only one immune measure (CD4 count) and one dopamine measure.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of DA in blood is less than 130 pM, while in human cerebrospinal fluid and urine the levels of DA are 5 nM [31]. Chekhonin et al concluded that in experimental parkinsonism, the measurement of catecholamines and their metabolites in urine can be considered as a biomarker to evaluate the situation of the dopaminergic nigrostriatal system of the brain [32].…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed, the relationship between central, peripheral, and urinary catecholamines is unclear; therefore, we cannot determine the specific origin of the NE and DA assessed in this study. Nonetheless, evidence indicating that past studies have successfully used urinary NE and DA analysis to provide markers of central and peripheral functioning [47–52] suggests that our preliminary findings may provide insight into the relationship between NE and DA and female sexual arousal responses during different emotion‐motivation states. Future studies may wish to assess NE and homovanillic acid (a DA metabolite), in plasma, as this methodology may offer a more accurate assessment of these catecholamines [43], although limitations of this methodology will also need to be carefully evaluated.…”
Section: Discussionmentioning
confidence: 77%
“…The study's authors concluded that peripheral sympathetic elevation in DA activity might represent a marker for central DA hyperactivity. Similarly, daily urinary excretion of NE and DA decreased significantly in denervated rats undergoing experimental Parkinson's disease, offering promise for evaluating the concentration of striatal DA during treatment for Parkinson's disease (characterized by low DA in the striatum) in experimental studies [48]. In humans, elevated spot NE urinary levels have shown a close relationship with women's stress over the course of the workday [49].…”
Section: Introductionmentioning
confidence: 99%